2018
DOI: 10.3727/105221617x15093738210295
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Adiponectin‐FGF15/19 Axis in Ethanol-Induced Inflammation and Alcoholic Liver Injury

Abstract: Alcoholic liver disease (ALD) is the most prevalent form of liver diseases, encompassing a spectrum of progressive pathological changes from steatosis to steatohepatitis to fibrosis/cirrhosis and hepatocellular carcinoma. Alcoholic steatosis/steatohepatitis is the initial stage of ALD and a major risk factor for advanced liver injuries. Adiponectin is a hormone secreted from adipocytes. Fibroblast growth factor (FGF) 15 (human homolog, FGF19) is an ileum-derived hormone. Adipocyte-derived adiponectin and gut-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…These results are also consistent with previous studies demonstrating that FGF19 increases metabolic rate and reduces adiposity in mice (38), acts as a postprandial, insulin-independent activator of hepatic glycogen and protein synthesis (11), regulates hepatic glucose metabolism by inhibiting the CREBperoxisome proliferator-activated receptor g coactivator-1a pathway (11), and improves glucose effectiveness through the hypothalamus-pituitary-adrenal axis (41,42). Given that FGF19 can stimulate adiponectin expression and production by adipose tissue (43) and that circulating adiponectin levels are increased after RYGB (44), it is possible that one of the mechanisms by which FGF19 and NGM282 improve NAFLD and NASH is the induction of adiponectin. Indeed, we have recently reported that selective activation of the FGFR1-bKlotho complex with an agonistic antibody increased serum adiponectin, and a high-molecular-weight form of adiponectin in particular, in obese patients (45).…”
Section: Discussionsupporting
confidence: 92%
“…These results are also consistent with previous studies demonstrating that FGF19 increases metabolic rate and reduces adiposity in mice (38), acts as a postprandial, insulin-independent activator of hepatic glycogen and protein synthesis (11), regulates hepatic glucose metabolism by inhibiting the CREBperoxisome proliferator-activated receptor g coactivator-1a pathway (11), and improves glucose effectiveness through the hypothalamus-pituitary-adrenal axis (41,42). Given that FGF19 can stimulate adiponectin expression and production by adipose tissue (43) and that circulating adiponectin levels are increased after RYGB (44), it is possible that one of the mechanisms by which FGF19 and NGM282 improve NAFLD and NASH is the induction of adiponectin. Indeed, we have recently reported that selective activation of the FGFR1-bKlotho complex with an agonistic antibody increased serum adiponectin, and a high-molecular-weight form of adiponectin in particular, in obese patients (45).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, FGF19 is involved in the feedback regulation of bile acid synthesis via potently reducing the hepatic activity of CYP7A1 [11], which plays a critical role in the communication between the small intestine and the liver [7]. FGF19 was proved to be correlated with the development and progression of alcoholic steatohepatitis [10]. Interestingly, we found that the lower serum FGF19 level was correlated with GI dysfunction complicated by ALI, and lower FGF19 than 52 μg/ml suggested a higher risk of occurrence of ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies indicated that reduced FGF19 levels are associated with ileal resection, diarrhea and disease activity, and FGF19 may as a biomarker for functioning ileum in Crohn's disease [8,9]. Adiponectin-FGF15/19 axis as an essential adipose-GI-liver coordinator involved in the development and progression of alcoholic steatohepatitis [10]. Furthermore, administration of a nontumorigenic FGF19 variant (M70) in healthy human volunteers represents an effective approach for the prevention and treatment of cholestatic liver diseases associated with bile acid dysregulation via potently reducing the hepatic activity of cholesterol 7a-hydroxylase (CYP7A1) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin levels were associated with the intensity of liver dysfunction and worse prognosis in patients with alcoholic liver disease, suggesting its potential as a prognostic biomarker [139]. Emerging evidence has revealed that dysregulated adiponectin-fibroblast growth factor (FGF) 15 (human homolog, FGF19) axis and impaired hepatic adiponectin-FGF15/19 signaling are associated with alcoholic liver damage in rodents and humans [140].…”
Section: Adiponectinmentioning
confidence: 99%